Aid for incumbents: The electoral consequences of COVID-19 relief - Jeffrey Clemens; Julia Payson; Stan Veuger (American Enterprise Institute (AEI), 2024)
The COVID-19 pandemic led to unprecedented levels of federal aid transfers to state governments. Did this funding increase benefit state incumbents electorally? Identifying the effect of revenue windfalls on economic voting is challenging because whatever conditions led to the influx of cash might also benefit or harm incumbent politicians for a variety of other reasons. We develop an instrument that allows us to predict allocations to states based on variation in congressional representation. We find that incumbents in state-wide races in 2020, 2021, and 2022 performed significantly better in states that received more relief funding due to their over-representation in Congress. These results are robust across specifications and after adjusting for a variety of economic and political controls. We consistently find that the pandemic-period electoral advantage of incumbent politicians in states receiving more aid substantially exceeds the more modest advantage these politicians enjoyed during pre-pandemic elections. This paper contributes to our understanding of economic voting and the incumbency advantage during times of crisis as well as the downstream electoral consequences of both the COVID-19 pandemic and of unequal political representation at the federal level.
Keywords: 330; COVID-19; Elections; Fiscal stimulus